Terrorist Attacks in Indonesia : Does Terrorism Work? - I Gusti Putu Bagus Pradana; Ihza Pamesti, Rere Cika (Sekolah Tinggi Ilmu Kepolisian, 2024)
This article aims to conduct an analytical examination of the terrorist attacks in Indonesia to assess the success of terrorism. The analysis uses a framework to evaluate the success and inherent advantages from a tactical, organizational, and strategic perspective. Notable cases analyzed include the Bali Bombings in 2002 and 2005; the Australia Embassy Bombing in 2004; the Jakarta Marriot and Ritz-Carlton Bombings in 2009; and the Jakarta assaults in 2016. These instances were selected based on their substantial influence on Indonesian culture and their portrayal of various terrorist strategies and goals. The implication indicates that although certain tactical objectives may be accomplished, there are typically restrictions on achieving strategic and organizational aims. This study explains tactical successes implied by immediate casualties and economic disruption. The study gives some recommendations to enhance intelligence efforts in counterterrorism, cooperation and collaboration with international efforts, and improving the deradicalization program. This insight can be used by policymakers and law enforcers who work with counter-terrorism efforts to make the efforts in Indonesia more effective.